Occupational mobility and risk factors in working men: selection, causality or both? Results from the GAZEL study. Issue 11 (4th November 2003) - Ribet, C; Zins, M; Gueguen, A; Bingham, A; Goldberg, M; Ducimetière, P; Lang, T
Abstract : Objective: To explore the relation between risk factors (RF) and occupational mobility in working men. Setting: 20 000 volunteers working at the French National Electricity and Gas Company (GAZEL cohort). Participants: Men aged 43 to 53 years in 1992. Design: Three designs were used for analysis. (1) The association between occupational mobility experienced before 1992 and RF reported at that date was analysed among 10 383 men. (2) The predictive role of RF on occupational mobility over 1992–1999 was studied in a subsample of 4715 men. (3) Reciprocally, occupational mobility in 1985–1992 was analysed in relation to RF changes over 1993–1999. Main outcome measures: Self reported smoking status, excessive alcohol consumption, arterial hypertension, and overweight. Occupational mobility defined by any upward transition between senior executives and professionals/middle executives/employees, and workers. Results: (1) Cross sectionally, non-mobile men as their entry into the company had a higher risk of being smokers, excessive alcohol drinkers, and overweight in 1992 than mobile men. (2) Longitudinally, smokers and excessive alcohol drinkers in 1992 had a higher risk of non-mobility than, respectively, non-smokers and non-excessive alcohol drinkers. (3) Non-mobile men in 1985–1992 had a higher risk of becoming smokers, excessive alcohol drinkers, and hypertensive in 1993–1999 than upwardly mobile men. Conclusion: These results suggest a complex relation between RF and occupational mobility. A high level of RF, particularly health behaviours, might account for a selection process reducing upward occupational mobility. In turn, a lack of upward occupational mobility might be associated with an increased incidence of RF.